Psychological characteristics of anxiety manifestations in children with rare diseases and craniofacial developmental anomalies: a comparative study - Tokarchuk Анастасія (Psychosomatic Medicine and General Practice, 2026)
Background. Patients with rare diseases or craniofacial developmental anomalies constitute a special category due to the presence of rare hereditary disorders that are often accompanied by congenital deformities of the face, head, and neck. Compared with patients in general pediatric hospitals, they tend to experience excessive self-criticism, difficulties in social interactions, and lower self-confidence. Objective. To investigate the characteristics and structure of anxiety in patients with rare diseases and craniofacial developmental anomalies compared with patients treated in a multidisciplinary pediatric hospital. Materials and Methods. This study analyzed the level and structure of anxiety in patients with rare diseases and craniofacial developmental anomalies compared with patients admitted to a multidisciplinary hospital. The research was conducted at the State Non-Profit Enterprise National Children’s Specialized Hospital "Okhmatdyt" of the Ministry of Health of Ukraine. A total of 205 patients aged 6–18 years (mean age: 12 years) participated in the study with informed consent obtained from both the children and their parents. Participants were divided into two groups. Group 1 included 103 patients with rare diseases and craniofacial developmental anomalies (49 girls and 54 boys). Group 2 consisted of 102 age-matched patients with general medical conditions (57 girls and 45 boys). No statistically significant demographic differences were observed between the groups. Anxiety was assessed using the Screen for Child Anxiety Related Emotional Disorders (SCARED) questionnaire, the Social Phobia Inventory (SPIN), and the State-Trait Anxiety Inventory (STAI). Statistical analysis was performed using the Mann–Whitney U test. Results. Statistically significant differences were found between the two groups across all anxiety measures (p < 0.001). Patients with rare diseases and craniofacial developmental anomalies demonstrated significantly higher anxiety scores: SCARED – 52 [47; 58] versus 22 [19.3; 25]; SPIN – 45 [25; 66] versus 27 [25; 33]; STAI state anxiety – 43 [37; 48.5] versus 37.5 [34; 42]; and STAI trait anxiety – 49 [41; 55] versus 41 [36; 44]. These findings indicate that anxiety represents a dominant component of the psychoemotional status of patients with rare diseases and craniofacial anomalies, manifesting as increased sensitivity to social evaluation and impaired social adaptation. In contrast, patients with general medical conditions predominantly demonstrated moderate anxiety levels. The findings may serve as a basis for developing and improving psychological support programs tailored to the specific needs of these patients. Conclusions. Elevated levels of both trait and social anxiety are characteristic psychological features of patients with rare diseases and craniofacial developmental anomalies. The findings support the necessity of developing specialized psychological support and intervention programs that address the individual psychological needs of this patient population. Keywords: anxiety, psychological characteristics of anxiety, rare diseases, craniofacial developmental anomalies, children, psychological support.